CONSIDERATION OF JUDGES IN DECIDING CASES OF DOMESTIC VIOLENCE CRIMES COMMITTED BY HUSBANDS TO WIVES COMMITTED BY HUSBAND TO WIFE - Saputra, Mahendra Agnur; Putri, Hanuring Ayu Ardhani; Khaerudin, Ariy (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
The purpose of this study is to examine the law enforcement and judges' consideration of the perpetrators of the crime of Domestic Violence committed by husband to wife in decision No. 233/Pid.Sus /2023/PN Ktg. This type of research uses descriptive qualitative with a normative juridical approach. Data collection using literature study. This research uses qualitative analysis with an interactive model. The results showed that law enforcement against perpetrators of domestic violence crimes that the defendant was sentenced to imprisonment for 4 (four) years. The judge's consideration in imposing a sentence on the crime of domestic violence was the beating committed by a husband to his wife in Decision No. 233/Pid.Sus/2023/PN Ktg is based on the testimony of witnesses, evidence and the testimony of the defendant, where the proof is sufficient if it is based on at least 2 (two) pieces of evidence plus the judge's belief.